Integrated Assessment Models of Climate Change Economics - Wang, Zheng; Wu, Jing; Liu, Changxin; Gu, Gaoxiang (Springer Nature Singapore : Imprint: Springer, 2017)
X, 181 p. 59 illus., 40 illus. in color.